2015
DOI: 10.1186/s40880-015-0017-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral anti–hepatitis B therapy on the survival of patients with hepatocellular carcinoma initially treated with chemoembolization

Abstract: IntroductionMost hepatocellular carcinomas (HCC) develop in a background of underlying liver disease including chronic hepatitis B. However, the effect of antiviral therapy on the long-term outcome of patients with hepatitis B virus (HBV)-related HCC treated with chemoembolization is unclear. This study aimed to evaluate the survival benefits of anti-HBV therapy after chemoembolization for patients with HBV-related HCC.MethodsA total of 224 HCC patients who successfully underwent chemoembolization were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In addition, some reports have shown that antivirus therapy for HBV-positive patients was associated with prolonged OS after TACE. 43 , 44 Similarly, antivirus therapy was an independent prognostic factor in both multivariate analyses and the Fine and Gray regression model for HCC patients in this study. It was also suggested that the combining H101 with antivirus therapy may increase curative effects for HCC patients after TACE therapy, which requires further investigation.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, some reports have shown that antivirus therapy for HBV-positive patients was associated with prolonged OS after TACE. 43 , 44 Similarly, antivirus therapy was an independent prognostic factor in both multivariate analyses and the Fine and Gray regression model for HCC patients in this study. It was also suggested that the combining H101 with antivirus therapy may increase curative effects for HCC patients after TACE therapy, which requires further investigation.…”
Section: Discussionsupporting
confidence: 56%
“…One study showed that sustained low HBV load below 2000 IU/mL was a strong protective factor for long-term DFS and OS after curative resection in HBV-related HCC [ 23 ]. In addition, the effect of NAs differs in patients with different tumor stages [ 16 , 29 ]. Therefore, HBV DNA level, tumor stage, and liver function should be considered before administration of NAs [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The add‐on resection and/or ablation significantly reduced the uncertainty of the HCC outcome and was only impacted by the vascular invasion. We strongly recommend the add‐on resection and/or ablation after TACE whenever the patient is eligible …”
Section: Discussionmentioning
confidence: 99%
“…We strongly recommend the add-on resection and/or ablation after TACE whenever the patient is eligible. 48,50,60,61 A limitation of this retrospective study is that the patients were all recruited from a single center. However, our results are encouraging and will be helpful in future studies designed to verify or extend our findings to improve the prognosis of unresectable HCC treated with TACE.…”
Section: Discussionmentioning
confidence: 99%